Analysis of Shape of Lingula in Dry Adult Human Mandible in a Bangladeshi Population - Ahmed, Muntasir; Akter, Mahfuza; Haque, Shah Md Atiqul; Ara, Rifat; Islam, Shamima; Lotif, Safat; Khanam, Farjana; Mili, Dilruba Afrose (Community Based Medical Journal, 2024)
The lingula is an important anatomical landmark used in oral and dental surgeries and to block the inferior alveolar nerve. Our study aims to analyze different types of lingula found in mandibles of Bangladeshi individuals. This cross-sectional, descriptive study was done on 150 fully ossified dry human mandibles in the Department of Anatomy, Mymensingh Medical College, Mymensingh, Bangladesh between July 2019 and June 2020. A non-random purposive sampling technique was adopted. The lingula was classified into four types: triangular, truncated, nodular and assimilated. The triangular shape was most commonly found (67%), followed by truncated (19.33%), nodular (9.66%) and assimilated (4%). On right side of the mandible, the triangular shape was present in 61.33% samples and on left side, in 59.33% samples. Truncated shape was found 25.33% on right side and 26.66% on left. Nodular shape was present in 10% on right side and 9.33% on left. Assimilated shape was observed in 3.33% on right side and 4.66% on left. Knowledge of various morphological shapes helps dental and maxillofacial surgeons to preserve important structures like inferior alveolar nerve and vessels during surgical interventions of mandible. Our data is expected to increase the information pool, which will be useful for further anthropological studies. CBMJ 2024 July: vol. 13 no. 02 P: 223-226